Usability and User Experience Evaluation of a Geriatric Care Screening Tool for Nursing Practice - Vita Lucya; Novya Aslahatul Mar’ah; Fitri Fauziah (STIKep PPNI Jawa Barat, 2026)
Background: Population aging continues to intensify the demand for comprehensive geriatric nursing assessments, particularly in primary care and community health settings. In many contexts, these assessments are still performed manually, which can be time-consuming, prone to documentation errors, and difficult to integrate into ongoing care planning. Digital screening tools may help address these challenges; however, their effectiveness largely depends on usability and user experience among frontline nurses. Objective: This study aimed to evaluate the usability and user experience of the Geriatric Care Screening Tool, a digital application developed to support geriatric nursing assessments, from the perspective of nurse users. Methods: A usability and user experience evaluation study was conducted using a descriptive quantitative design within a user-centered development framework. Twenty nurses involved in geriatric nursing services participated in the evaluation. User needs were explored through a focus group discussion (FGD), followed by expert content validation of the application. Usability was assessed using the System Usability Scale (SUS), while user experience was evaluated using the User Experience Questionnaire (UEQ). Data were analyzed descriptively and interpreted using established benchmark standards. Results: The mean SUS score was 70.38, indicating marginally acceptable usability with a “Good” adjective rating. UEQ results showed positive user experience across all dimensions. The highest scores were observed in Clarity (1.75), Accuracy (1.20), and Stimulation (1.04). Lower scores were identified in Attractiveness (0.73), Efficiency (0.86), and Novelty (0.65), suggesting areas that require further improvement, particularly related to interface design, navigation speed, and innovative features. Conclusion: The Geriatric Care Screening Tool demonstrated acceptable usability and a generally positive user experience among nurses. While the application meets basic functional requirements for geriatric nursing assessment, further refinement—particularly in efficiency, visual design, and innovation—is needed to optimize its use in clinical and community practice.